(untitled) (Biological Sciences - PJSIR, 2003)
Levels of Cd, Cr, Fe, Pb and Zn were determined in water and fish samples from three different locations in the Benin river. The sampling points were chosen such that Gbokoda, a village between Koko and Ogheye where a flow station (Olague flow station or crude oil well) is situated serves as a pollution point source and Koko as a baseline concentration point. Three species of fish each, that are top feeder, Tilapia mariae (which is herbivorous and feeds mainly on floating phytoplankton), middle feeder, Pseudotolithus elongatus (that is ominivorous) and bottom feeder, Chrysichthys nigrodigitatus (also ominivorous) were used for the study. The mean wet weight of the species sampled at the different locations ranged between 385.17 - 417.44g. The maximum concentration levels observed in water samples for Cd, Cr, Fe, Pb and Zn were 3.50 x 10- 4 g/l, 1.24 x 10- 3 g/l, 3.10 x 10- 3 g/l and 1.50 x 10- 3 g/l, respectively. The mean concentration levels determined for the various species of fish are: for Cd, Tilapia mariae 7.30 x 10- 5 , Pseudotolitus elongatus 8.67 x 10- 4 and Chrysichthys nigrodigitatus 1.581 x 10- 4, for Fe, Tilapia mariae 5.500 x 10- 3 , Pseudotolithus elongatus 4.700 x 10- 3 and Chrysichthys nigrodigitatus 3.9133 x 10- 3, for Pb, Tilapia mariae 4.4240 x 10- 3 , Pseudotolithus elongatus 3.4100 x 10- 3 and Chrysichthys nigrodigitatus 9.6730 x 10- 3 for Zn, Tilapia mariae 5.467 x 10- 3 , Pseudotolithus elongatus 5.067 x 10- 3 and Chrysichthys nigrodigitatus 8.833 x 10- 3. (All values are g/g of fish)